Peranan Muhammadiyah Bidang Majelis Dikdasmen dalam Pengelolaan SMA di Kota Makassar - Mukdar Boli (el-Idarah: Jurnal Manajemen Pendidikan Islam, 2020)
This research: The Role of the Elementary Education Board Section (Dikdasmen) of Muhammadiyah in Senior High Schools Management in Makassar City. This research entitled The Role of the Elementary Education Board Section (Dikdasmen) of Muhammadiyah in Senior High Schools Management in Makassar City. It discusses the role of the Muhammadiyah Dikdasmen Council in managing senior high schools in Makassar. In this issue, the author described many things, they are: the problems which exist in the management of SMA in Makassar City, how the role of the Elementary Education Board Section (Dikdasmen) of Muhammadiyah in managing senior high schools, how are the supporting and inhibiting factors which appear in Dikdasmen Council in Muhammadiyah Senior High School management in Makassar.To answer those problems, the data collection in the field was carried out by using techniques of observation, interviews and documentation. The observation and the interview use some guidelines. The sources of data were selected from the Muhammadiyah Elementary Education Board Section (Dikdasmen) in Makassar, the Muhammadiyah Senior High School Principal, the teaching staff, and the leaders of Muhammadiyah of Makassar City. The approaches which are used in this research are normative theological approach, pedagogical approach, and psychological approach. After the process of data collection, data processing, and data analysis, the results of this study are: there are some problems found, such as the lack of funds, the lack of facilities and infrastructure, and the weak arrangement. The Elementary Education Board Section (Dikdasmen) of Muhammadiyah in Makassar has a role in managing the Muhammadiyah High School. In addition, there are also supporting factors from the society, a sincere and trustful spirit from educators, school committees and staff in reviving Muhammadiyah Senior High Schools. The implication of this research is Dikdasmen assembly needs to pay attention to operational policies to improve performance in carrying out mandated tasks, educational facilities and infrastructure as soon as they are equipped. Moreover, they need to provide educational services which is oriented to the needs and satisfaction of the society, and create a conducive climate to encourage healthy competition which is in harmony with the interests and expectations of the society.